2018
DOI: 10.1111/hiv.12675
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of virological failure in HIV‐1‐infected patients switching to dolutegravir maintenance monotherapy

Abstract: Objectives The Dolutegravir Monotherapy for HIV (DOMONO; NCT 02401828) study showed that maintenance monotherapy with dolutegravir ( DTG ) is associated with virological failure ( VF ) and leads to DTG resistance and as a result should not be used. However, data on clinical and virological factors associated with VF during DTG monotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…The eight studies of persons receiving dolutegravir monotherapy for treatment simplification included three trials with 211 persons, three cohort studies with 92 persons, and two case reports 28–35 (Table 3). Overall, 16 persons developed VF and an INSTI resistance mutation.…”
Section: Resultsmentioning
confidence: 99%
“…The eight studies of persons receiving dolutegravir monotherapy for treatment simplification included three trials with 211 persons, three cohort studies with 92 persons, and two case reports 28–35 (Table 3). Overall, 16 persons developed VF and an INSTI resistance mutation.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with a nadir CD4 count ≤ 200 cells/lL have been found to have a higher risk of virological failure on monotherapy [9]. In such patients, lower sCD14 levels and similar values of the other biomarkers studied were found in patients on dual therapy for 48 weeks compared with patients receiving ongoing triple therapy.…”
Section: Discussionmentioning
confidence: 90%
“…Hence, in the last few years, antiretroviral therapy (ART) simplification strategies have provided alternative treatments for the aging HIV‐1‐infected population with increasing rates of comorbidities . While several studies of dual therapy have suggested adequate long‐term efficacy and tolerability with fewer adverse events or have demonstrated noninferior efficacy compared with triple therapy , concerns about the possibility of increased residual viraemia, and increased systemic inflammatory activity and immune activation, are still present, as previously described for monotherapy strategies . This issue requires to be addressed urgently, in order to prevent possible suboptimal treatment in otherwise well‐treated, suppressed patients.…”
Section: Introductionmentioning
confidence: 99%
“…32 These results were in accordance with predictive factors of virological response in deintensification studies. 33,34 A recent trial of deintensification retained HIV DNA quantification as an inclusion criteria, with a threshold of <2.7 log 10 copies/10 6 PBMCs. 35 In our cohort, no impact on virological outcome was found of detection of new resistance on DNA GRT in patients virologically suppressed.…”
Section: Discussionmentioning
confidence: 99%